Pelatihan Deteksi Neuropati Dengan Teknik Ipswich Touch Test pada Pasien Diabetes Melitus: Neuropathy Detection Training Using Ipswich Touch Test Technique For Diabetes Mellitus Patients - Aminuddin, Aminuddin; Baiq Emy, Nurmalisa; Hasbunsyah, Siregar (Jurusan Keperawatan Politeknik Kesehatan Kementerian Kesehatan Palu, 2023)
Introduction: Diabetic neuropathy is a complication of diabetes that occurs quite often with a percentage of 28.7-39.5%. One of the efforts to reduce this number is early detection, which can be done by the general public. Early detection using the IpTT method has been shown to be safe, simple, requires no equipment, and can be done publicly. The purpose of this social service is to train health cadres to detect diabetic neuropathy using the IpTT method. Methods The service team implements this public service activity by applying the methods of lecture, discussion, demonstration and face-to-face training among the participants. This activity took place on Saturday, July 10, 2021, in the nursing class D3 of the Palus Tervishoiu Professional University. The target group of this activity is 36 health cadres representing 18 posbindus. Results: After the training and IpTT preparatory demonstration, the mean posttest score was 80 and was good in the IpTT preparatory skill category. Due to these results, it is necessary to periodically conduct IpTT trainings to update and improve the knowledge and skills of the cadres in conducting IpTT examinations. This educational activity using IPTT technology to detect diabetic neuropathy can be used as one program in the Talis Health Center area to reduce the number of amputations in diabetic patients.